Postcolonial Feminism Discourse in Pramoedya Ananta Toer’s Novels - Rahmayati, Rahmi (UPT Pusat Penerbitan LP2MPP ISI Bali, 2025)
The portrayal of Indonesian women during the colonial era cannot be separated from the construction of the patriarchal and the colonial system, which gave rise to the burden of colonization and double oppression during that period. However, this did not deter Indonesian women from their struggle and resistance against the patriarchal and colonial system of the time, even though some were unable to secure their rights, both as women and as human beings. This is represented in Pramoedya Ananta Toer's novels. This study aims to explore Pramoedya Ananta Toer's thoughts on women in his works (in the form of novels) that intersect with the issues of feminism and colonialism. These works include the novels Gadis Pantai, Larasati, and Bumi Manusia. This study uses a qualitative method with a postcolonial feminism theory approach. The data analysis techniques in this study are (1) identifying; (2) classifying; (3) describing; (4) analyzing; and (5) drawing conclusions. The results of the study indicate that women face a double burden of colonization and oppression. This is because women are victims of both patriarchal and colonial systems. Furthermore, despite being caught between these two systems, they continue to struggle and resist both.